Indoleamine 2,3-Dioxygenase 1: A Promising Therapeutic Target in Malignant Tumor - Song, Xiaotian; Si, Qianqian; Qi, Rui; Liu, Weidan; Li, Miao; Guo, Mengyue; Wei, Lin; Yao, Zhiyan (Frontiers in Immunology, 2021)
Tumorigenesis is a complex multifactorial and multistep process in which tumors can utilize a diverse repertoire of immunosuppressive mechanisms to evade host immune attacks. The degradation of tryptophan into immunosuppressive kynurenine is considered as an important immunosuppressive mechanism in the tumor microenvironment. There are three enzymes, including TDO, IDO1, IDO2 involved in the metabolism of Tryptophan. IDO1 has a wider distribution and higher activity in catalyzing tryptophan than the other two, therefore, it has been studied most extensively. IDO1 is a cytosolic monomeric, heme-containing enzyme, which is now considered as an authentic immune regulator and represent one of the promising drug targets for tumor immunotherapy. Collectively, this review highlights the regulation of IDO1 gene expression and the ambivalent mechanisms of IDO1 on the antitumoral immune response. Further, new therapeutic targets via regulation of IDO1 are discussed. A comprehensive analysis about the expression and biological function of IDO1 can help us to understand therapeutic strategies of the inhibitors targeting IDO1 in malignant tumor.